Oostenbrinkellus gen. n. and a new species of the rare nematode genus Lawtonema Siddiqi, 1998 (Nematoda: Dorylaimida: Tylencholaimoidea) from the Western Ghats - Islam, Md Niraul; Ahmad, Wasim (Zootaxa, 2024)
One new genus and a new species belonging to the superfamily Tylencholaimoidea from the Western Ghats, India are described and illustrated. Oostenbrinkellus gen. n. is characterized by being a medium sized nematode with a 0.92–1.3 mm long body; lip region cap-like with distinct labia disc; amphidial fovea cup-shaped, aperture occupying about two-thirds to four-fifths of the lip region diameter; odontostyle 10.5–12.0 µm long, slender, slightly sinuate, mid region bent slight dorsally, anterior beak-like, with a distinct ventral stiffening piece covering the posterior half of the ventral arm; its aperture about one-fifth of the odontostyle length, 1.6–2.0 times the lip region diameter long; odontophore 7.5–9.0 µm long, with distinct basal knobs, total stylet 18.5–20.5 µm; pharynx consisting of an anterior slender part, expanding posteriorly into a short cylindrical basal bulb, 19–25% of total pharyngeal length; female genital system mono-opisthodelphic with anterior uterine sac; tail long filiform both the sexes; males with 24–29 μm long spicules. Lawtonema indicum sp. n. is characterized by having a 1.25–1.28 mm long body; lip region cap-like with distinct labial disc; amphidial fovea cup-shaped, aperture occupying about three-fourths of the lip region diameter; odontostyle 10–10.5 μm long, its tip bent dorsally; odontophore 9.5–10 μm long, total stylet length 19.5–20.0 μm; pharynx expanding gradually into a short cylindrical bulb, 19–20% of total pharyngeal length; female genital system amphidelphic; tail long filiform; male with 24 μm long spicules.